2009
DOI: 10.1183/09031936.00167707
|View full text |Cite
|
Sign up to set email alerts
|

The role of neutropenia on outcomes of cancer patients with community-acquired pneumonia

Abstract: Although the presence of neutropenia may predispose cancer patients to develop community-acquired pneumonia, the role of neutropenia on their outcomes has not been investigated. The purpose of the present study was to compare clinical outcomes of cancer community-acquired pneumonia patients with and without neutropenia.Patients with cancer, identified in the Community-Acquired Pneumonia Organization database, were divided into two groups according to the type of cancer and the presence of neutropenia: patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
4
8
0
Order By: Relevance
“…However, among cancer patients, neutropenia did not influence time to clinical stability, length of hospital stay or in-hospital mortality. The study by ALIBERTI et al [21] is in agreement with most of the studies reported over the last decade, in which neutropenia has supplied no prognostic information in cancer patients with acute respiratory failure [22,23], even those requiring mechanical ventilation [24,25]. However, neutropenia has been associated with outcomes in studies focusing on the overall population of critically ill cancer patients [26][27][28].…”
supporting
confidence: 79%
See 2 more Smart Citations
“…However, among cancer patients, neutropenia did not influence time to clinical stability, length of hospital stay or in-hospital mortality. The study by ALIBERTI et al [21] is in agreement with most of the studies reported over the last decade, in which neutropenia has supplied no prognostic information in cancer patients with acute respiratory failure [22,23], even those requiring mechanical ventilation [24,25]. However, neutropenia has been associated with outcomes in studies focusing on the overall population of critically ill cancer patients [26][27][28].…”
supporting
confidence: 79%
“…In this issue of the European Respiratory Journal, ALIBERTI et al [21] compare clinical outcomes of cancer patients admitted for community-acquired pneumonia with (n573) or without (n5135) neutropenia. Overall, community-acquired pneumonia patients with cancer were found to have higher mortality rates than communityacquired pneumonia patients without cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the cases are related to neutropenic condition. During the past decades, the attention in management of infections in cancer patients has focused on fever and neutropenia [6][7][8]. However, latest guidelines by the National Comprehensive Cancer Network recommend that immunocompromised non-neutropenic cancer patients should receive equal attention as those with neutropenia [9].…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic drugs used for the treatment of lung cancer can affect chemotactic and phagocytic function, without reflecting on the total cell count. The functional capabilities of phagocytes such as neutrophils, eosinophils and mononuclear cells may be intrinsically defective even before the initiation of chemotherapy [6].…”
Section: Discussionmentioning
confidence: 99%